2017
DOI: 10.1002/cnma.201700291
|View full text |Cite
|
Sign up to set email alerts
|

A NiCo2O4 Shell on a Hollow Ni Nanorod Array Core for Water Splitting with Enhanced Electrocatalytic Performance

Abstract: Nickel cobaltite (NiCo 2 O 4 ) nanostructures have been considered as promising bifunctional electrocatalyst materials for the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in alkaline electrolyte. However, the activity of these materials toward overall water splitting is still unsatisfactory because a larger voltage is needed to drive the reactions. This study shows that more-efficient bifunctional catalysts based on NiCo 2 O 4 materials can be obtained by adopting an integrated compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…48 However, the electrocatalytic ability of such pristine TMOs in HER is still unsatisfactory. To break the bottleneck, several approaches have been developed, including doping, 52,134,135 defect (oxygen vacancy) engineering, 50,51 crystal-plane engineering, 49 compositing 48,124,126,136 and hierarchical structuring. 137 146 Figure 8f).…”
Section: Transition Metal Oxidesmentioning
confidence: 99%
“…48 However, the electrocatalytic ability of such pristine TMOs in HER is still unsatisfactory. To break the bottleneck, several approaches have been developed, including doping, 52,134,135 defect (oxygen vacancy) engineering, 50,51 crystal-plane engineering, 49 compositing 48,124,126,136 and hierarchical structuring. 137 146 Figure 8f).…”
Section: Transition Metal Oxidesmentioning
confidence: 99%
“…22,23 For example, Wang et al reported a novel hollow core-shell Ni@NiCo 2 O 4 to improve the electronic conductivity of NiCo 2 O 4 owing to the hollow Ni directly attached to the conductive Ni foam. The hollow core-shell Ni@NiCo 2 O 4 electrode showed excellent catalytic activity with a current density of 10 mAcm −2 at a bias of 1.58 V. 24 These are not enough to reveal the catalytic nature and helpful to ARTICLE Journal Name 2 | J. Name., 2012, 00, [1][2][3] This journal is © The Royal Society of Chemistry 20xx…”
Section: Introductionmentioning
confidence: 99%
“…The NiFe5 sponge exhibits the lowest Tafel slope of 82 mV dec −1 among the various NiFe sponge and close to the value of the Pt/C catalyst (52 mV dec −1 ), indicating a faster HER catalytic kinetics. The Tafel slope and η 10 values of NiFe5 electrode are also on par with the several recently reported HER electrocatalysts (Table ) . Further, in order to evaluate the electron‐transfer kinetics of the electrodes, EIS measurements were performed.…”
Section: Resultsmentioning
confidence: 65%
“…Among the various alternatives, hydrogen (H 2 ) is considered as a promising and viable resource for future due to its high specific energy density and almost zero pollution on combustion, and recent studies showed its techno‐economical viability too . Among the various approaches of H 2 generation, electrochemical water splitting has attracted the attention of researchers and is considered as one of the most effective and eco‐friendly approaches than other conventional H 2 generation methods . The process of splitting water involves two‐half cell processes namely the oxygen evolution reaction (OER) and the hydrogen evolution reaction (HER), which involve multi‐electron transfer reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation